Association of occupational exposure on semen density in male industrial workers undergoing infertility treatment at tertiary care hospital - Wadhwa, Leena; Fauzdar, Ashish; Wadhwa, Sanjana N.; Singh, Lata; Chakravarti, Sumit; Kaur, Onkar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Working with particular substances or under certain working situations may cause some workers to experience abnormalities in their sexual or reproductive health. Occupational exposures can lead to infertility, but the workers may not be aware of such problems. The purpose of the study was to determine the association between male infertility and occupation of industrial workers in organized sector. Methods: Prospective case-controlled study that included 136 industrial workers working in organized sector and attending infertility clinic for treatment. This study included male partners aged between 21-46 years with primary or secondary infertility and undertaking same occupation for at least last three months. Complete infertility workup of all male partners attending infertility clinic was done that included detailed history and information related to occupation. Routine semen parameters were evaluated according to the 2010 World Health Organization (WHO) criteria. Results: In the present study, significant semen abnormalities were observed in male partners with age more than 31 years and undertaking arduous jobs for more than 5 years (p <0.05) in study group (n=136) as compared to control group (n=62). The abnormal semen count were observed in 114 (83.2%) workers in the study group that included 43 (31.6%) with total sperm concentration (TSC) less than 10 million/ml and azoospermia in 44 (32.3%). Reduced motility (asthenozoo-spermia) was observed in majority 125 (91.9%) of male partners. The findings were significant (p <0.05) as compared to control group. Conclusions: Preventive measures in the workplace need to be established to reduce the effect of occupational hazards and its influence in the semen parameters ultimately leading to infertility.